A near-frictionless and extremely elastic hydrogenated amorphous carbon film with self-assembled dual nanostructure - Liu, Xiaoqiang (Advanced materials (Deerfield Beach, Fla.), 2012)
Copyright © 2012 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.